DAMPAK KEBIJAKAN BEA KELUAR CPO TERHADAP INDUSTRI CPO DAN TURUNANNYA (IMPACT OF CPO EXPORT TAX POLICY ON CPO INDUSTRIES AND DERIVATIVE - Erizal Mahatama, Leo Mualdy C S dan Umar Fakhrudin, Aziza R Salam, Bagas Haryotejo (Pusjar SKPP Lembaga Administrasi Negara, 2014)
Imposition of export duty policy for CPO and its derivative products is animportant policy Imposition of export duty policy for CPO and its derivativeproducts is an important policy of promoting the growth of national industry. This policy will affect the upstream and downstream sides. This study examines the impact of the policy impositionof export duty CPO products and derivatives which can provide a more positive welfare impact, than has been achieved so far, furthermore determined the appropriate policies to be applied to compensate the aggrieved stakeholders, to determine the distribution of surplus between producers and consumers. The applied method is the analysis of the economic impact, wich is cost and benefit using a simulation. Based on simulation results, manufacturers have lost the opportunity to obtain a windfall gain, while the government gained revenue from export duties due to reduced smuggling. In order to award compensation to the manufacturer, the facility / amenity that is returned including the improvement of transport infrastructure (roads andports), research and development (R & D), promotion and advocacy abroad, human resource development, especially farmers through training, meeting the needs of farmers (seeds, fertilizers and land titling) in order to revitalize oil palm plantations, and facilities / other relevant ease.Keywords : impact policy, export tax, CPOKebijakan pengenaan bea keluar untuk produk CPO dan turunannya merupakan kebijakan yang penting dalam mendorong pengembangan industri nasional. Kebijakan ini akan mempengaruhi sisi hulu dan hilir. Kajian ini bertujuan melihat dampak kebijakan pengenaan bea keluar produk CPO dan turunannya dapat memberikan dampak kesejahteraan yang lebih positif dari yang telah dicapai saat ini. Selain itu, ingin melihat kebijakan apa yang perlu diterapkan untuk mengkompensasi pemangku kepentingan yang dirugikan oleh kebijakan ini, serta net welfare- untuk mengetahui distribusi surplus antara produsen dan konsumen. Metode yang digunakan adalah analisis dampak ekonomi yaitu cost and benefit dengan simulasi. Berdasarkan hasil simulasi, produsen mengalami kehilangan kesempatan memperoleh windfall gain secara maksimal, sedangkan pemerintah memperoleh pendapatan dari bea keluar akibat berkurangnya smuggling. Dalam rangka pemberian kompensasi bagi produsen, maka fasilitas/kemudahan yang dikembalikan diantaranya adalah perbaikan infrastruktur transportasi (jalan dan pelabuhan), penelitian dan pengembangan (R & D), promosi dan advokasi di luar negeri, pengembangan sumber daya manusia, khususnya petani melalui pelatihan, pemenuhan kebutuhan petani (bibit, pupuk dan sertifikasi lahan) dalam rangka revitalisasi kebun kelapa sawit, dan fasilitas/kemudahan lain yang relevan. Kata kunci : dampak kebijakan, bea keluar, CPO